Management of encrusted ureteral stent: nine years experience in a single center - Ab Rashid, Islah Munjih; O., Wahida; MDM, Ashraf; MNG, Rahman (2010)
lntroduction: Ureteral stent insertion is common in urological practice. However, ureteral stent is not without complications or adverse effects. Stent migration, infection, fragementation and encrustation are among the known complicationso f ureterals tents. Objective: To share our experience in the management of stentse ncrustationi n our centre. Material and methods: We retrospectively studied all patients with ureteral stent encrustation which needed intervention either surgically or by ESWL in our centre (HospitalU niversitiS ainsM alaysia).F or a periodo f 9 years (zooz-zoto)a, ll patientsw ith stent encrustationw ho needed surgical or ESWL interventions were included in the study. Demographic data, risk factors and outcome of treatments were studied.T reatmentd ecisionsw ere made basedo n the clinicala nd imagingf indings. Results: 36 patients were included in the study. Mean age at presentation was 48.47 years. There were 2i males and t5 females. The stents were inserted for stone diseases alone(8o.6%)c, ombination of stone diseasesa nd ureteric strictures('n.'t%u),r eteric strictures alone(5.6%a) nd in a case of malignant disease(2.82). The treatment options were ESWL, vesicolitholapaxy, vesicolithotripsy, ureteroscopy, retrograde intra renal surgery (RIRS) and PCNL. All the stents were successfully removed. 583% of the stents were removed in a singles ession.T he rest of the stents needed additional interventions. Conclusion: Eventhough stent insertion is fundamental in urological practice it is not without complications.S tent should only be inserted in patients who are really in need for the stent insertion. However, stent encrustation could still be successfulltyr eated even in the very severec ases